Mediation: Application and Functioning under Shariah and Law - Attaullah, Qazi; Saqib, Lutfullah (Islamic Studies, 2017)
This study debates mediation as a tool of amicable resolution of civil and criminal disputes, in legal spectrum of shariah and law. It, primarily, investigates the subject from four dimensions. First, it traces the history of mediation to the ancient societies and explores the earliest forms of mediation. Second, it sheds light on the meaning of mediation by analysing various approaches of the experts of alternative dispute resolution (ADR) towards it. Here, the discussion, predominantly, moves round the technical sense of mediation and the complications it involves. It also explores mediation in shariah and searches out its meaning, focusing on its preferred connotation and the advantages it has brought about. Third, the study explains the subject matter of mediation, ascertains its limits as prescribed by jurists (fuqaha). Notably, it proposes the criterion for suitability or otherwise of a case for mediation and denounces the theory that civility and criminality of a dispute determines such criterion. More importantly, it justifies the application of mediation to criminal issues, including matters coming within the domain of hudud. In this regard, it rather for the first time successfully differentiates between hudud offenses and hudud cases, in terms of legal effects and ultimate consequences. Fourth, it focuses on the functioning of mediation with specific reference to Pakistani legal system. The study marks out the causes of poor productivity of mediation in law on the one hand, and explains the functioning of mediation and its quality results in shariah, on the other. Suggestions and proposals for improvement have also been given at appropriate places.